Keterampilan Guru dalam Mengelola Kelas pada Pembelajaran Qur'an Hadits di MTs Nurul Huda Sidoarjo - Tsalis Febrianti Muthoharotun Nisa`; Wildan Fahmi Febriansyah; Abdullah Zaini (Madaniyah, 2024)
Abstrak Skills in managing a class are things that must be owned by a teacher, because if the teacher does not master skills in managing a class, then he will not achieve learning objectives, the teacher is the spearhead in successfully managing a class, to achieve this success the teacher must be skilled, carry out tasks and its role as a facilitator, class manager, learning implementer, and curriculum driver. This study aims to find out how the influence of teacher skills in managing classes on the effectiveness of student learning at MTs Nurul Huda Sidoarjo. The method in the research was conducted using qualitative methods, and the research design used was a case study, while the tools for collecting data used observation and interviews. Based on the results of research and discussion conducted by researchers. It is known if classroom learning is carried out by teachers in theory they know their role. However, in practice and especially the role of Al-Quran Hadith subject teachers, there are still obstacles in carrying out their role as it should be in class management. So this needs to be corrected immediately so that learning can run well. Keywords: Teacher Skills, Classroom Management, Student Learning Effectiveness